My first sewing book 35 easy and fun projects for children aged 7 years old + - Akass, Susan (CICO Kidz, 2011)
Presents an introduction to the basic techniques of sewingand provides instruction for thirty-five beginner projects for such items as a rag doll, sock monster, felted bag, patchwork pincushion, embroided jeans, and hair barrettes.